Single-ended and differential voltage controlled oscillator - Xiong, Yifang. (2012)
A voltage-controlled oscillator (VCO) is one of the most essential building blocks in the analog and digital circuits world. Among all kinds, there are many different implementations of VCOs. One of them is a ring oscillator based VCO, which is commonly used in the clock generation subsystem. The main reason of ring oscillator’s popularity is a direct consequence of its easy integration. Due to their integrated nature, ring oscillators have become an essential building block in many digital and communication systems. They are used as voltage-controlled oscillators (VCO’s) in applications such as clock recovery circuits for serial data communications, disk- drive read channels, on-chip clock distribution, and integrated frequency synthesizers. The design of a ring oscillator involves many tradeoffs in terms of speed, power, area, and application domain.